Romanticism and Realism: The Mythology of Nineteenth-Century Art - Rosen, Charles; Zerner, Henri (New York Viking, 1984)
Traces the split during the early nineteenth century between avant-garde and academic art, examines the work of Caspar David Friedrich, Thomas Bewick, and Thomas Couture, and discusses the impact of photography on art
Keywords: 19th Century (1801-1900); Fine art